Institutional operating figures in basic and applied sciences: Scientometric analysis of quantitative output benchmarking - Fischer Axel; Kölzow Silvana; Kreiter Carolin; Scutaru Cristian; Groneberg-Kloft Beatrix; Quarcoo David (BMC, 2008)
Abstract Background Institutional operating figures and benchmarking systems are important features for the implementation of efficacy in basic and applied sciences. They are needed for research evaluation and funding policy. However, the current policy settings for research evaluation urgently need review since there may be imbalances present in many areas. Methods The present study assessed benchmarking of research output. By the use of large data bases research output was categorized and analyzed. Specific areas of major research activity were identified by comparing publication density on different organ systems and inter- and intrafield comparison was performed for selected countries. Results Novel density-equalizing mappings were constructed that illustrate trends of publication activity and identify subsets of major interest in a total of 5,527,558 published items. A dichotomy was present between Western countries such as the US, UK or Germany and Asian countries such as Japan, China or South Korea concerning research focuses. Conclusion The present study is the first large scale analysis of global research activity and output over the last 50 years. The presently described assessment of operating figures at the national and international level can be used to identify single areas of research that are heavily focused. Further research on qualitative output benchmarking is needed to improve current policy settings for research evaluation.